2014
DOI: 10.1155/2014/305942
|View full text |Cite
|
Sign up to set email alerts
|

Absorbed Radiation Dose in Radiosensitive Organs Using 64- and 320-Row Multidetector Computed Tomography: A Comparative Study

Abstract: Aim. To determine absorbed radiation dose (ARD) in radiosensitive organs during prospective and full phase dose modulation using ECG-gated MDCTA scanner under 64- and 320-row detector modes. Methods. Female phantom was used to measure organ radiation dose. Five DP-3 radiation detectors were used to measure ARD to lungs, breast, and thyroid using the Aquilion ONE scanner in 64- and 320-row modes using both prospective and dose modulation in full phase acquisition. Five measurements were made using three tube vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Accumulated evidence has demonstrated that oxidative stress in different tissues is the underlying mechanism of radiation damage. The results of extensive studies have demonstrated that the thyroid gland is a radiosensitive organ (Khan et al, 2014) and that the exposure to ionizing radiation may induce thyroid disorders (Zhai et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence has demonstrated that oxidative stress in different tissues is the underlying mechanism of radiation damage. The results of extensive studies have demonstrated that the thyroid gland is a radiosensitive organ (Khan et al, 2014) and that the exposure to ionizing radiation may induce thyroid disorders (Zhai et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the examination room, the adult phantoms have been placed on the table and, with the aid of laser lights; they were oriented so that their central axis passed through the isocenter of the gantry during the table displacement [19,20]. They central area of the phantoms were scanned in helical mode with voltages of 120 and 135 kV using the system automatic control, electrical current in automatic, in the rage of 50 to 500 mA [12,13,20].…”
Section: Scanning Protocolsmentioning
confidence: 99%
“…17 There have been reports that when the same area is imaged, the DAP in CBCT is similar to the CT dose index in multidetector CT without a moving cradle. [18][19][20][21] The data acquired from group B images were approximately half of the data acquired from group A images. However, the DAP values observed in group B were reduced by approximately 70% compared with the patients in group A.…”
Section: Acquisition Time and Binning In Clinical Subsets A And Bmentioning
confidence: 99%